PERANCANGAN SISTEM INFORMASI PENGOLAHAN DATA NILAI SISWA PADA LEMBAGA KURSUS ENGLISH COURSE JAKARTA MENGGUNAKAN METODE WATERFALL - Henny Destiana; Novita Indriyani (Paradigma, 2011)
English course and training is an educational institution that organizes English courses independently with its own data processing. System processing power value is very important to do. The problem that often occurs among long processing time data search and still the kerangkapan data. The design of the system is needed to address these issues include the DAD (Data Flow Diagram), ERD (Entity Relationship Diagram), Normalization and Waterfall methods. On the normalization will form four tables include tables of students, teachers tables, classroom tables and tables of values. The results of the transition system is a computerized system, so the data processing students particularly value the student as the final result (output) of the learning process conducted by the students. Key words : Information system, Scores Processing System, ERD, Waterfall